2012
DOI: 10.1007/s12262-012-0529-1
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Cecum: An Incidental Finding

Abstract: To hypothesize that mobile cecum is a rare etiological factor and cecopexy is the choice of treatment in patients with recurrent right lower abdominal pain. Prospective study was conducted in the department of general surgery, SSG Hospital, Baroda, from January 2008 to December 2009. Patients with recurrent right lower abdominal pain were planned for appendectomy. In those patients with intraoperative findings suggestive of macroscopically normal appendix while cecum found to be mobile and no other gross abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…This is related to the anatomical position of the appendix of the developmental stage of the intestinal rotation. 8 After extensive research in the literature, only a citation of a case in Turkish magazine, 1965, without digitized version, of appendicitis in epigastric hernia was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is related to the anatomical position of the appendix of the developmental stage of the intestinal rotation. 8 After extensive research in the literature, only a citation of a case in Turkish magazine, 1965, without digitized version, of appendicitis in epigastric hernia was found.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the acute inflammatory response (appendicitis) and subsequent intra-abdominal events (localization, adhesion and abscess) and the presence of a previous (epigastric) defect could explain this presentation. 8 Another explanation in such circumstances is appendicitis as a result of extrinsic pressure, strangulation, and necrosis within the hernia defect.…”
mentioning
confidence: 99%
“…However, when MCS is symptomatic, it predisposes to volvulus in 50% of cases . It is not clear what degree of detachment is enough to cause painful rotation …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in 10% of the population, there might be an anatomical variation and abnormal cecum mobility otherwise referred to as mobile cecum syndrome [5]. In such individuals, the lateral peritoneal attachment of cecum is either absent or so mobile that terminal ileum and cecum can be found in any quadrant of the abdomen depending on the position and activity of the patient [6]. In addition, acute inflammatory response (appendicitis) and subsequent intraabdominal events (localization, adhesion and abscess) and the presence of a prior defect (paraumbilical) could explain such presentation.…”
Section: Discussionmentioning
confidence: 99%